足関節底屈筋トレーニングは脳性麻痺児・者の歩行を改善する - 石原 みさ子; 樋口 由美; 出原 千寛 (理学療法学, 2012)
Purpose: We examined our hypothesis that a 7-week program of plantar flexor training improves gait function, by using spatiotemporal and Center of pressure (COP) parameters. Subject: Three subjects with cerebral palsy (13.7 ± 5.4 years old), who are possible to serial walk 10 m or more, and understand oral instructions, were included in the study. Methods: We employed a single-subject ABA' design consisting of a 7-week baseline phase, a 7-week intervention phase, and a 7-week post intervention phase. The subjects were given training 3 times a week during the intervention phase. Result: Two cases showed a significant improvement in the walking ability and the walking efficiency, one case showed a significant improvement in the walking efficiency. These results support our hypothesis. Conclusion: It is not easy to improve gait function by increasing the amount of the activity of the muscle for people with cerebral palsy who have not haven a normal movement pattern since their birth. However, the approach of the amount which has been a contraindication, is one of the important approaches for it to improve and maintain gait function. 【目的】我々は7週間の足関節底屈筋トレーニングが脳性麻痺児・者の歩行機能を改善するという仮説を,歩行能力を示す時間距離変数と歩行効率を示す足圧中心(COP)変数を用いて検討した。【対象】10m以上の連続歩行が可能で,口頭指示が理解できるCP児・者3名(13.7±5.4歳)。【方法】ABA'型のシングルケースデザィンを用い,それぞれの期間を7週間ずつ設定した。介入期には,足関節底屈筋トレーニングを週3回7週間自宅で行った。【結果】2症例は,歩行能力と歩行効率に有意な改善,1症例は歩行効率に有意な改善を示し,我々の仮説を支持する結果となった。【結論】生まれながらに正常な運動パターンを学習していないCP児・者は,筋の活動量を増加させることで歩行を改善することは容易でない。しかし,従来は禁忌とされていた量の取り組みが,歩行機能を維持・改善するための重要な取り組みのひとつであると考える。